Flood and Landslide Hazard Mapping in Teluk Baguala District, Ambon City, Indonesia - Rakuasa, Heinrich; Stewart Pertuack (Journal of Scientific Insights, 2025)
Teluk Baguala District, Ambon City is frequently affected by flood and landslide disasters. This study uses the Maximum Entropy method to model flood and landslide hazard areas based on environmental variables and the spatial distribution of disaster occurrences. The flood mapping results show that areas with low vulnerability cover the largest area, totaling 5,296.07 hectares, while medium-risk areas cover only 188.84 hectares, and high-risk areas cover 493.97 hectares. The area with low landslide vulnerability reaches 2,595.19 hectares, whereas medium vulnerability areas are smaller at 2,327.26 hectares, and very vulnerable or high-risk areas cover only 694.73 hectares. The flood validation test shows an AUC value of 0.974, while the landslide AUC value is 0.851. These mapping results are expected to assist the government in flood and landslide disaster mitigation efforts in the future.